THE PROTECTION OF TRADITIONAL KNOWLEDGE UNDER INDONESIAN PATENT LAW: BETWEEN OPPORTUNITIES AND CHALLENGES - Yulia, Yulia (UI Scholars Hub, 2021)
The protection of traditional knowledge through patents is still an interesting issue on an international level. Indonesia revised Patent Law in 2016 (Law Number 13 of 2016 concerning Patent or Indonesian Patent Law). This Law has confirmed that patent is an exclusive right that the country gives for the inventor to the invention in technology, for a certain amount of time, to implement itself or give other parties to implement it. The patent can be submitted if required terms of the patent application, there are novelty, inventive steps, and industrially applicable. That provision cannot be fulfilled by traditional knowledge, where traditional knowledge is the knowledge passed down from generation to generation. This study is a doctrinal study that will analyze Article 26 of the Indonesian Patent Law. The study found that Indonesia has required the mention of sources of origin in traditional knowledge under Indonesian Patent Law. This article provides opportunities for the protection of traditional knowledge. It is also a challenge for communities to obtain protection and benefit-sharing from traditional knowledge that the original source has stated when filing a patent.